Guilt and its relationship with the self-awareness Educational research Open Educational College Students (Journal Of Educational and Psychological Researches, 2015)
Targeted current research study of the relationship between guilt and self-consciousness and consisted of the research community of students from the open educational college, as has been selected students in the Department of Counseling and psychological science department and the researcher used guilt, prepared Scale (Ansari, 2003), and the measure of selfawareness prepared (Shammari 0.2000), and extracted his Alsekoumtria characteristics, Fastkhrjt alternatives after a presentation to a group of experts and specialists in the field of psychological counseling psychology, education, science and psychological validity and reliability Alvakronbach manner and retesting reaching reliability coefficient of guilt ((0.85) and awareness of self (0.76) For the purpose of verification of the goals of research, the researcher used statistical means the following:Pearson correlation coefficient-1samples t-test (T-taste)-2The researcher reached the following conclusions. The open educational college students enjoy a high level of guiltThe presence of statistically significant differences between feelings of guilt and selfawareness is an inverse relationshipIn light of the search results put the researcher set of recommendations are: -Strengthening the different approaches and diverse activities that promote proper human behavior and the search for the best ways that contribute to the development and development. -Take advantage of students who have a very high level of guilt and remorse in the leadership of the various social activities inside and outside the university.-The possibility of a briefing based on psychological counseling and educational research results and guidance by directing students who are concerned about the lack of security and various social activities and urged them to exercise them.Finally, the researcher suggested doing a series of studies in the following sequence:-Building a program to raise the level of guilt among different age groups and all academic levels  -Measure the level of guilt for students in all stages of public education (elementary - and middle - and lower secondary)